Full Mouth Rehabilitation with Dental Implants- A Case Report - M. Magar, Swaroop Kumar (International Research in Medical and Health Sciences, 2020)
The objective of full mouth rehabilitation is not only the reconstruction and restoration of the worn-out dentition but also the maintenance of the health of the entire stomatognathic system.Some patients simply cannot wear dentures at all. Their quality of life is hampered. For such patients, an implant-supported removable or fixed prosthesis is the only hope. Implant prosthesis has the ability to restore normal function, aesthetic, speech, and comfort of such patients.The aim of the study is to present a case report on implant-supported fixed prosthesis used for full mouth rehabilitation.